Analisis dan Pengembangan Sistem Pengendalian Intern atas Penjualan Jasa (Studi Kasus pada Bandung Giri Gahana Golf & Resort) - Ari Permana; Sugih Sutrisno Putra (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The Internal Control System is one of the controls in managing the sale of services. Effective and efficient management of SPI for the sale of services will reduce fraud that occurs in the company. As in Bandung Giri Gahana Golf & Resort, SPI is still not effective because there is still lack of supervision and the implementation of an SOP by the frontliner. Therefore an evaluation is needed to assess how effective and efficient the existing SPI is, and recommendations needed to improve existing SPI . Researchers in this study will conduct evaluation and analysis and design SPI recommendations in Bandung Giri Gahana Golf & Resort by using qualitative descriptive methods of case study approaches and data collection is done by documentation, observation and interviews. The SPI recommendation that the author makes is the Standard Operational Procedure (SOP). Based on research that the existing SPI is adequate. However, there are still a number of elements that are not yet adequate, so the authors recommend SPI on these elements to maximize the existing SPI.